ANALISIS KONSEP IDEOLOGI POLITIK ISLAM PERSPEKTIF SAYYID QUTB DALAM TAFSIR FI ZILAL AL-QUR’AN - Moh. Jufriyadi Sholeh; Iwan Ghufroni (Yayasan Baitul Hikmah al-Zain, 2026)
This research examines the concept of Islamic political ideology from the perspective of Sayyid Qutb, motivated by contemporary debates on the relationship between religion and the state as well as the growing dynamics of political Islam in modern society. The research focuses on two key concepts, namely ḥākimiyyah (divine sovereignty) and jāhiliyyah (human sovereignty), as elaborated in the Tafsir Fi Zilal al-Qur’an. This study employs a qualitative approach using library research methods, involving the collection and analysis of data from relevant primary and secondary sources. The findings reveal that ḥākimiyyah emphasizes that legitimate law originates solely from God, while jāhiliyyah refers to systems of life not based on divine law.